Preparation method of full-flexible PZT film and preparation method of full-flexible PZT sensor
By constructing a mica/LSMO heterostructure on a fluorogold mica substrate, high-quality preparation and lossless release of fully flexible PZT films are achieved, and the problems of high cost and structural damage in traditional methods are solved, and a high-performance and ultra-sensitive fully flexible PZT sensor is obtained.
Patent Information
- Application Number
- CN202411499302.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
AI Technical Summary
Currently, high-performance sensors that adopt high-quality flexible ferroelectric films with high-cost methods are still facing challenges, and traditional physical/chemical release methods have problems of structural damage and interface chemical bond strengthening.
Using fluorogold mica substrate and lanthanum strontium manganese oxygen (LSMO) as substrates and sacrificial layers, the LSMO coating was constructed by spin coating and pyrolysis to achieve high-quality growth and lossless release of PZT films.
It realizes low-cost and high-quality fully flexible PZT film preparation and cost-effective PZT film transfer, and obtains high-performance and ultra-sensitive fully flexible PZT sensors, improving ferroelectric, piezoelectric performance and mechanical flexibility.
Smart Images

Figure CN119522023A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric sensors, and in particular to a method for preparing a fully flexible PZT film and a method for preparing a fully flexible PZT sensor. Background Art
[0002] With the continuous development and progress of science and technology and society, the next generation of smart electronic products has put forward higher requirements for the portability and flexibility of sensors. Flexible electronics is an emerging electronic technology that makes organic / inorganic electronic devices on flexible / ductile substrates, with excellent lightness, comfort and bendability. Compared with traditional electronics, flexible electronics have greater flexibility and can adapt to different working environments to a certain extent and meet the deformation requirements of equipment. Therefore, they are increasingly widely used in many fields, such as communications, biomedicine, etc.
[0003] Flexible piezoelectric sensors, as one of the representative works of flexible electronic products, are involved in many wearable smart application scenarios. For example, in health monitoring, flexible piezoelectric sensors can better convert extremely small movements such as heartbeat, diaphragm activity and breathing movement into electrical signals.
[0004] However, the inherent brittleness and rigidity of the substrate limit the further application of piezoelectric sensors in the above scenarios. For example, the piezoelectricity of lead zirconate titanate film (PZT, a type of inorganic perovskite structure) with high electromechanical conversion performance usually needs to be crystallized at high temperature (greater than 700°C, much higher than the melting point of most flexible substrates) to manifest, so this type of PZT film usually needs to be built on a substrate that is resistant to high temperatures but has a small maximum elastic strain (such as SrTiO3, LaAlO3 and Si). However, these rigid and brittle substrates not only limit the mechanical flexibility of ferroelectric films, but also suppress the large strain caused by the electric field, resulting in the piezoelectric coefficient d33 being much smaller than the corresponding ceramic or single crystal.
[0005] Based on this, some new strategies for growing or transferring inorganic perovskite structured films onto flexible substrates have emerged in recent years. For example, metals and mica have certain flexibility and good high temperature resistance, and have been proven to be flexible substrates for the growth of inorganic perovskite structured films. However, due to the lack of lattice matching, inorganic perovskite structured films grown on these substrates often exhibit low fatigue resistance. Not only that, their inherent toughness still prevents electronic devices from forming conformal contact with the human body, which can lead to distortion of sensing signals.
[0006] Mechanical peeling and chemical release are advanced technologies for separating thin films from rigid substrates. A pioneering example is that Park's team used laser peeling technology to release a 2-micron-thick PZT film from a sapphire substrate and transferred it to a plastic substrate, achieving excellent flexibility and output performance, but this physical release method inevitably causes structural damage. The chemical release method involves growing a film on a sacrificial layer and then removing the sacrificial layer through a selective chemical etching process to release the film. Compared with mechanical peeling, the chemical release method usually causes less damage during the transfer process and retains the structural quality of the released film. However, the typical chemical release process is usually carried out on expensive single-crystal substrates, which requires complex pretreatment of the substrate to obtain an atomically flat surface, and the strong chemical bonds between the interfaces make the sacrificial layer more difficult to remove, which limits its industrial application.
[0007] Therefore, it remains a great challenge to obtain high-performance sensors based on high-quality flexible ferroelectric films in a cost-effective manner. Summary of the invention
[0008] The present invention discloses a method for preparing a fully flexible PZT film and a method for preparing a fully flexible PZT sensor, which realizes low-cost, high-quality fully flexible PZT film preparation and cost-effective PZT film transfer, and obtains a high-performance, ultra-sensitive fully flexible PZT sensor.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a fully flexible PZT film comprises the following steps:
[0011] (1) uniformly depositing an LSMO coating on a fluorophlogopite substrate and crystallizing the LSMO coating;
[0012] (2) Spin coating several layers of PZT thin film on the crystallized LSMO coating to obtain a PZT / LSMO / mica product;
[0013] (3) preparing a flexible support layer on the PZT thin film layer;
[0014] (4) Immersing the product obtained in step (3) in an etching solution to completely dissolve the LSMO coating, thereby obtaining a fully flexible PZT film.
[0015] Specifically, the step (1) comprises the following steps:
[0016] (101) preparing LSMO sol;
[0017] (102) 0.2–0.7 M LSMO sol was spin-coated onto the surface of a fluorophlogopite mica substrate and pyrolyzed at 100–300 °C for 10–50 min to uniformly deposit an LSMO coating;
[0018] (103) The fluorophlogopite substrate deposited with the LSMO coating was placed in a tube furnace and heated to 650–1000 °C at a rate of 1–10 °C / min in an oxygen atmosphere with a flow rate of 30–40 mL / min and kept at this temperature for 1–3 h to crystallize the LSMO coating.
[0019] Furthermore, the step (101) comprises the following steps:
[0020] (1011) 8 mmol of manganese acetate tetrahydrate and an equal mole of acetylacetone were added to 10 mL of anhydrous methanol, stirred to dissolve, and then 5.6 mmol of lanthanum nitrate hexahydrate was added to prepare precursor A;
[0021] (1012) 2.4 mmol of strontium acetate pentahydrate was added to 5 mL of anhydrous methanol and L-lactic acid was added dropwise at a twice molar ratio. After stirring and dissolving, precursor B was obtained.
[0022] (1013) Precursors A and B were mixed and diluted to 20 mL with anhydrous methanol. The mixture was magnetically stirred for 8 h and then aged for 24 h to obtain LSMO sol.
[0023] Specifically, the step (2) comprises the following steps:
[0024] (201) The PZT sol was spin-coated on the crystallized LSMO coating and the organic solvent in the sol was removed to obtain a PZT thin film layer;
[0025] (202) Repeat step (201) 20-24 times to obtain a PZT / LSMO / mica product of target thickness; wherein, after each two spin coatings, the product is placed in a rapid annealing furnace and sintered at 600-800° C. in an oxygen atmosphere for 6-8 minutes.
[0026] Specifically, the step (3) comprises the following steps:
[0027] (301) Polymethyl methacrylate is added to ethyl lactate and stirred in an oil bath at 150–200 °C for 5–7 h to obtain a PMMA solution with a mass fraction of 5–20 wt.%.
[0028] (302) spin coating the PMMA solution onto the surface of the PZT / LSMO / mica product and baking;
[0029] (303) Repeat step (3) 4 times, wherein the baking temperature for the first three times is 50-100°C and the last time is 90-120°C, to obtain a solidified flexible support layer with uniform thickness.
[0030] Specifically, in step (4), the etching solution is obtained by mixing high-purity water, hydrogen chloride and potassium iodide.
[0031] Based on the above fully flexible PZT film, the present invention also provides a method for preparing a fully flexible PZT sensor, comprising the following steps:
[0032] S1. Design interdigital electrodes and print them on PET substrates;
[0033] S2. Transfer the above fully flexible PZT film to a PET substrate, and then perform packaging and polarization to obtain a fully flexible PZT sensor.
[0034] Specifically, the step S1 includes the following steps:
[0035] S101. Use drawing software to design interdigitated electrodes, where the interdigital spacing is 500 μm, the finger width is 200 μm, and the finger length is 7.4 mm;
[0036] S102, using an inkjet printer to print interdigitated electrodes on a PET substrate.
[0037] Furthermore, the printing ink used was conductive silver ink, and each interdigitated electrode was printed repeatedly 4 times. After printing, the sample was placed in an oven for baking to remove the solvent of the ink.
[0038] Furthermore, in step S2, the process of transferring the piezoelectric film to the PET substrate is as follows:
[0039] a. Insert the piezoelectric film obliquely into anhydrous ethanol, and separate the PZT / PMMA film from the fluorphlogopite substrate by means of the capillary force of ethanol;
[0040] b. Immerse the PET substrate printed with interdigital electrodes in ethanol, lift up the floating PZT / PMMA film, and complete the transfer.
[0041] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0042] (1) Different from the expensive and rigid single crystal substrate used in the traditional physical / chemical release strategy, the present invention uses a fluorphlogopite substrate as the substrate, which is not only inexpensive and easy to prepare, but also has an atomically smooth surface. Then, lanthanum strontium manganese oxide (LSMO) is used as a sacrificial layer. By optimizing the pyrolysis temperature of the LSMO sol, LMSO is uniformly deposited (grown) on the fluorphlogopite substrate, thereby constructing a mica / LSMO heterostructure. In this heterostructure, on the one hand, LMSO is uniformly deposited on the fluorphlogopite substrate, which can provide suitable lattice and thermal matching conditions for the high-quality growth of the PZT thin film layer; on the other hand, since there is no strong chemical bonding at the interface between mica and LSMO, the clamping effect of the mica substrate is not strong, and LMSO can be easily removed by chemical methods, which is conducive to the non-destructive release of the subsequent thin film. Through this cost-effective transfer strategy, the fully flexible piezoelectric film obtained in the present invention achieves comprehensive improvements in ferroelectric, piezoelectric properties and mechanical flexibility, and can release almost lossless PZT / PMMA films to low-modulus polyethylene terephthalate substrates (PET).
[0043] Experiments show that, thanks to the PZT film preparation and transfer scheme adopted by the present invention, combined with the excellent deformation ability and high-voltage electrical activity of the low-modulus PET substrate, the residual polarization rate of the transferred PZT film in the present invention is increased by 57%, and the effective piezoelectric coefficient is increased by 43%. Furthermore, the sensing sensitivity of the fully flexible piezoelectric sensor prepared by the present invention in the two motion modes of bending and compression is also greatly improved.
[0044] In summary, this fully flexible piezoelectric sensor with greatly improved comprehensive performance shows great potential in wearable portable electronic products and can be well applied to smart products such as real-time respiratory monitoring and wireless gesture recognition.
[0045] (2) Since independent PZT films are very fragile, especially PZT films with nanometer-level thickness, they will be macroscopically broken by the fluctuation of the etching solution flow or the slight pulling of tweezers during the transfer process. Therefore, the present invention prepares a flexible support layer on the PZT film layer to play a protective role and facilitate the subsequent complete transfer of the PZT film.
[0046] (3) Since the film structure after etching is very fragile, it is impossible to grow interdigital electrodes on the surface by magnetron sputtering technology. Therefore, the present invention presets interdigital electrodes and cleverly uses inkjet printing to print these interdigital electrodes on the PET substrate. Then, the capillary force of ethanol is used to separate the PZT / PMMA film from the fluorphlogopite substrate to obtain the PZT / PMMA film, which is finally transferred to the PET substrate printed with the interdigital electrodes. The above process is not only convenient to operate, but also with the heterostructure design of mica / LSMO, the PZT / PMMA film can be separated from the fluorphlogopite substrate almost without loss and quickly transferred to the PET substrate. Moreover, because ethanol has the characteristic of fast volatilization, using ethanol as the transfer medium can also shorten the waiting time between the transfer and packaging processes.
[0047] (4) The various links of the present invention are closely linked, complementary and closely related. Through an innovative and cost-effective transfer strategy, a fully flexible PZT sensor with high performance and ultra-sensitivity is obtained on a flexible PET substrate, which not only improves the excellent electrical properties of the perovskite structure film, but also shows higher mechanical flexibility. Therefore, the present invention is very suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a simplified diagram of the preparation process of the fully flexible PZT film in Example 1 of the present invention.
[0049] Figure 2 This is a surface microscopic morphology of the sacrificial layer prepared in Example 1 of the present invention.
[0050] Figure 3 This is the grazing incidence XRD pattern of the sacrificial layer prepared in Example 1 of the present invention.
[0051] Figure 4 This is a microscopic cross-sectional view of the sacrificial layer prepared in Example 1 of the present invention.
[0052] Figure 5 This is a schematic diagram of the roughness characterization of the sacrificial layer prepared in Example 1 of the present invention, wherein: Figure 5 (a) AFM morphology of the sacrificial layer; Figure 5 (b) Figure 5 (a) Schematic diagram of the height fluctuation of the film at the position of the horizontal line segment (orange).
[0053] Figure 6 These are the XRD scanning results of the PZT / LSMO / mica product and LSMO / mica in Example 1 of the present invention.
[0054] Figure 7 This is the XPS analysis diagram of the PZT film surface before and after etching in Example 1 of the present invention.
[0055] Figure 8 The surface microscopic morphology of the PZT film before and after etching in Example 1 of the present invention, wherein: Figure 8 (a) is a schematic diagram of the surface of the PZT film before etching; Figure 8 (b) is a schematic diagram of the surface of the PZT film after etching.
[0056] Fig. 9 This is a SEM microscopic cross-sectional view of the PZT film before and after etching in Example 1 of the present invention, wherein: Fig. 9 (a) is the SEM microscopic cross-section image of the PZT film before etching; Fig. 9 (b) is the SEM microscopic cross-sectional image of the PZT film after etching; Fig. 9 (c) is the EDS result of the cross section of the PZT film after etching.
[0057] Fig.10 Schematic diagram of the roughness characterization of the PZT film before and after etching in Example 1 of the present invention, wherein: Fig.10 (a) is the AFM morphology of the PZT film before etching; Fig.10 (b) is the AFM morphology of the PZT film after etching; Fig.10 (c) Fig.10 (a) Schematic diagram of the height fluctuation of the film at the position of the horizontal line segment (green); Fig.10 (d) Fig.10 (b) Schematic diagram of the height fluctuation of the film at the position of the horizontal line segment (cyan).
[0058] Fig.11 This is the PFM zigzag phase diagram of the PZT film before and after etching in Example 1 of the present invention, wherein: Fig.11 (a) is the PFM zigzag phase image of the PZT film before etching; Fig.11 (b) is the PFM zigzag phase image of the PZT film after etching.
[0059] Fig.12 Schematic diagram of the phase loop and amplitude loop of the PZT film before and after etching in Example 1 of the present invention, wherein: Fig.12 (a) is the phase loop and amplitude loop of the PZT film before etching; Fig.12 (b) is the phase loop and amplitude loop of the PZT film after etching.
[0060] Fig.13 Schematic diagram of the hysteresis loop of the PZT film before and after etching in Example 1 of the present invention, wherein: Fig.13 (a) is the hysteresis loop of PZT film before etching; Fig.13 (b) is the hysteresis loop of the PZT film after etching; Fig.13(c) P of PZT film before and after etching under the same electric field max With P r .
[0061] Fig.14 This is a simplified diagram of the preparation process of the fully flexible PZT sensor in Example 4 of the present invention.
[0062] Fig.15 This is a graph showing the voltage signal test results of the fully flexible PZT sensor in Example 4 of the present invention under the knocking mode, wherein: Fig.15 (a) is the open circuit voltage test result of the sensor under different external forces; Fig.15 (b) is the voltage sensitivity test result of the sensor.
[0063] Fig.16 This is a graph showing the result of using a fully flexible PZT sensor to charge a capacitor in Example 4 of the present invention, wherein: Fig.16 (a) The case where capacitors with different capacities are charged to 22.5V; Fig.16 (b) shows the case of charging capacitors of different capacities for 3 minutes.
[0064] Fig.17 This is a graph showing the voltage signal test results of the fully flexible PZT sensor in cantilever beam mode in Example 4 of the present invention, wherein: Fig.17 (a) is the open circuit voltage test results of the sensor at different bending angles; Fig.17 (b) is the voltage sensitivity test result of the sensor.
[0065] Fig.18 This is a graph of positive and negative voltage waveforms when the fully flexible PZT sensor is bent downward and upward in Example 4 of the present invention.
[0066] Fig.19 This is a schematic diagram of a 3M mask equipped with a fully flexible PZT sensor to monitor breathing status in Example 5 of the present invention, wherein: Fig.19 (a) is the monitoring result when the subject breathes rapidly; Fig.19 (b) is the monitoring result when the subject breathes normally; Fig.19 (c) is the monitoring result when the subject coughs; Fig.19 (d) is the monitoring result when the subject takes a deep breath.
[0067] Fig. 20 This is a schematic diagram of the open circuit voltage signal of the smart glove equipped with a fully flexible PZT sensor in Example 6 of the present invention for recognizing different gestures. DETAILED DESCRIPTION
[0068] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.
[0069] Example 1
[0070] This embodiment provides a fully flexible PZT film, which is made of a fluorphlogopite substrate as a substrate, LSMO as a sacrificial layer, and PZT as an oxide film. Figure 1 As shown, the specific preparation process is as follows:
[0071] 1. Preparation of sacrificial layer
[0072] 1. Preparation of LSMO sol: Add 8 mmol of manganese acetate tetrahydrate and an equal molar amount of acetylacetone to 10 mL of anhydrous methanol, stir and dissolve, then add 5.6 mmol of lanthanum nitrate hexahydrate to prepare precursor A; then, add 2.4 mmol of strontium acetate pentahydrate to 5 mL of anhydrous methanol and dropwise add twice the molar ratio of L-lactic acid, stir and dissolve to obtain precursor B; finally, mix precursors A and B, dilute to 20 mL with anhydrous methanol, continue magnetic stirring for 8 h, and then let stand for 24 h for use.
[0073] 2. Deposition of LSMO coating: Use a pipette to absorb 0.4M LSMO sol and drop it onto the surface of a 1cm×1cm fluorphlogopite substrate. After spin coating and pyrolysis (pyrolysis temperature is 200°C), the LSMO coating is evenly deposited. Then, the fluorphlogopite substrate with the LSMO coating is placed in a tube furnace, and in an oxygen atmosphere with a flow rate of 30mL / min, the temperature is raised to 850°C at a rate of 5°C / min and kept for 2h to crystallize the LSMO coating, thereby obtaining a sacrificial layer.
[0074] Figure 2 The surface microscopic morphology of the prepared sacrificial layer shows that within a larger scanning range, the surface of the sacrificial layer is flat and uniform. After magnification, it can be observed that the grains grow densely without obvious cracks and pores.
[0075] Figure 3 The physical phase and morphology of the prepared sacrificial layer are characterized by grazing incidence XRD patterns. It can be seen that the characteristic diffraction peaks of the sacrificial layer are sharp, and diffraction peaks appear at diffraction angles of 23.3°, 32.9°, 41.1°, 47.4° and 58.7°, corresponding to (012), (104), (202), (024) and (214) crystal planes, respectively. There are no other diffraction peaks, indicating that the LSMO coating has good crystallinity and no other impurities are generated.
[0076] Figure 4The microscopic cross section of the prepared sacrificial layer shows that the LSMO grains grown on the surface of the fluorphlogopite substrate are obvious and closely arranged. The thickness of a single sacrificial layer is about 160nm.
[0077] Figure 5 The roughness characterization results of the prepared sacrificial layer are shown, where Figure 5 (a) shows that within the scanning range of 1 μm × 1 μm, the grains of the sacrificial layer are obvious, the maximum height difference is within 40 nm, and the average surface roughness is 3.97 nm. Figure 5 (b) Figure 5 (a) The height of the film at the position of the horizontal line segment (orange) fluctuates, and the local height difference is within 30nm, indicating that the grain size on the surface of the sacrificial layer is relatively obvious.
[0078] 2. Preparation of PZT / LSMO / mica products
[0079] 1. Pb 1.1 Zr 0.52 Ti 0.48 The O3 (PZT) sol is spin-coated on the crystallized LSMO coating, and the organic solvent in the sol is removed to obtain a PZT thin film layer. In this embodiment, a slow and fast application process is set during spin coating, wherein the slow process allows the sol to evenly spread and cover the entire LSMO surface, and the fast process removes excess sol to obtain a PZT thin film layer with uniform thickness; the method for removing the organic solvent is: after spin coating, the sample is transferred to a 140°C and 380°C heating plate for pyrolysis for 5 minutes respectively.
[0080] 2. Repeat the above process 20 times, and after each spin coating, place the product in a rapid annealing furnace and sinter at 700°C for 6 minutes in an oxygen atmosphere to finally obtain a PZT / LSMO / mica product of target thickness (wherein the thickness of the PZT thin film layer is about 700nm).
[0081] Figure 6 The grazing incidence XRD patterns of PZT / LSMO / mica and LSMO / mica are shown. It can be seen that the characteristic diffraction peaks of the PZT film correspond to the PDF card one by one and the peaks are sharp, proving that the PZT film has good crystallinity. In addition, a small diffraction peak appears on the right side of the (110) peak of PZT, which is consistent with the Figure 3 After comparison, it can be seen that it is the (104) peak of LSMO.
[0082] 3. Preparation of Flexible Support Layer
[0083] 1. Add polymethyl methacrylate (PMMA) to ethyl lactate and stir in an oil bath at 150°C for 6 hours to obtain a PMMA solution with a mass fraction of 15wt.%. In order to facilitate the observation of the coating of the PMMA solution on the sample, a small amount of rhodamine B can be added to dye the PMMA solution.
[0084] 2. Use a pipette to draw 60 microliters of PMMA solution and drop it on the surface of the PZT / LSMO / mica sample, and spin-coat to obtain a support layer of uniform thickness. The spin-coated sample is placed on a heating table for drying to promote the solidification of the PMMA support layer and improve the adhesion between the PMMA and PZT thin film layers to prevent the two from separating in the subsequent etching and peeling steps.
[0085] 3. Repeat the spin coating 4 times, where the first three baking temperatures are 80°C and the last temperature is 100°C. In this way, a solidified flexible support layer with uniform thickness can be obtained. The flexible support layer has a total of 4 layers of PMMA with a certain thickness and can be spread out in the etching solution without wrinkles.
[0086] 4. Etching of the sacrificial layer
[0087] The product with the flexible support layer is immersed in the etching solution, and the LSMO coating reacts with the etching solution: La 0.7 Sr 0.3 MnO3+H2O+5HCl+KI=MnCl2+Cl2+12I2+KOH+3H2O+La 0.7 Sr 0.3 Cl, so that the LSMO coating is completely dissolved, and a fully flexible PZT film is obtained. In this embodiment, the etching solution formula used is: 200 mL of high-purity water, 5 mL of hydrogen chloride and 4 mg of potassium iodide, which are fully mixed and then left to stand for use.
[0088] In addition, in order to further increase the etching rate, the beaker containing the etching solution and the sample was placed in a water bath at 50° C. for heating.
[0089] Electrical performance test of PZT thin film before and after etching:
[0090] 1. In order to verify whether etching will cause damage to the PZT film, the element binding energy analysis of the PZT film surface before and after etching was performed by XPS. Figure 7 It can be seen that the film before and after etching contains four elements: Pb, Zr, Ti and O. The binding energy of the elements does not change significantly before and after etching, indicating that the etching solution has little damage to the surface structure of the film.
[0091] 2. Figure 8 The surface micromorphology of the PZT film before and after etching is shown. Figure 8(a) shows the surface of the PZT film before etching. There are no obvious cracks and holes. The PZT grains are uniform in size and densely distributed. Figure 8 (b) is the surface of the PZT film after etching, which still maintains a relatively obvious grain distribution, indicating that the etching process did not cause obvious damage to the film, ensuring the density and integrity of the film.
[0092] 3. Fig. 9 The SEM microscopic cross section of the PZT film before and after etching is shown. Fig. 9 (a) is a PZT / LSMO film grown on a fluorophlogopite substrate before etching. When the junction of the two films is magnified, it can be seen that there is a clear stratification under the PZT, proving that it is the LSMO layer. The cross section of the PZT film is flat, and the overall thickness is uniform, with an average thickness of about 700nm. The thickness of the PZT film after etching has not changed, but the upward side is now the side that was originally close to the LSMO. When the LSMO is etched by the etching solution, the surface morphology of the PZT film left behind should be complementary to it. Fig. 9 In (b), it can be seen that the upper edge of the PZT film is relatively rough after etching, which is also related to Figure 5 The results in are consistent. Fig. 9 (c) is the EDS result of the cross section of the PZT film after etching. It can be seen that the Pb, Zr, and Ti elements are evenly distributed in the film without obvious segregation. The O element is evenly distributed in the entire scanning range because the organic substrate at the bottom also contains oxygen.
[0093] 4. Fig.10 The roughness analysis results of PZT films before and after etching are shown. Fig.10 (a) The PZT film grains are closely arranged before etching, and the grain boundaries are obvious. Fig.10 (c) It can be seen that the maximum height fluctuation occurs at the grain boundary, ranging from about 10nm. At the same time, the average surface roughness of the PZT film is reduced to 1.37nm. Compared with the LSMO surface, the roughness is much better, indicating that the growth of the PZT film is conducive to improving the flatness of the film surface. This is because the PZT film grown layer by layer during the spin coating process fills the gaps on the LSMO surface and grows with the help of the LSMO grain nodules, finally obtaining a PZT film with a flat and smooth surface. The morphology of the PZT film after etching is shown in Figure 1. Fig.10 As shown in (b), the maximum height fluctuation is 60nm and the average surface roughness is 5.72nm. Compared with the PZT film before peeling, the smoothness is reduced, but it is comparable to the surface roughness of the LSMO film. Fig.10 The local height difference of (d) is 20 nm, indicating that the etching process has little effect on the surface morphology of the PZT film.
[0094] 5. The ferroelectric properties of the PZT film before and after etching were tested, and the results were as follows: Fig.11 As shown. -12V and +12V bias voltages were applied to the 3μm×3μm and 1μm×1μm regions, respectively. The PZT film before and after etching had a change in ferroelectric domain orientation, and the U-shaped boundary was clear, which closely corresponded to the applied electric field range, indicating that the film had few defects and no increase in lateral leakage conductance, proving that the etching process did not damage the ferroelectric properties of the film.
[0095] 6. Fig.12 The phase loop and amplitude loop of the PZT film before and after etching show that the PZT film before and after etching shows a complete phase loop and butterfly curve, proving that the film has a good local ferroelectric response. Before etching, the PZT film reached an amplitude of 30mV under a bias voltage of 12V, but after etching, the maximum amplitude rose to 43mV, an increase of 43%, indicating that the ferroelectric response of the PZT film was greatly improved after it was separated from the clamping effect of the substrate.
[0096] 7. Fig.13 The comparison results of the hysteresis loop of PZT film before and after etching. Fig.13 (a) and Fig.13 It can be seen from (b) that as the external electric field increases, the saturation polarization intensity and residual polarization intensity of the PZT film before and after etching increase continuously, and the ferroelectric polarization of the PZT film after etching is higher. Fig.13 (c) shows the variation trend of the saturation polarization intensity and remnant polarization intensity of the PZT film before and after etching. max and P r Both increase with the increase of electric field, but the residual polarization intensity of the film after etching is higher than the saturation polarization intensity before etching. Under the electric field intensity of 65kV / cm, the residual polarization intensity after etching is 43μC / cm2, which is 2.11 times that before etching.
[0097] Example 2
[0098] The difference from Example 1 is that in this embodiment:
[0099] 1. Use a pipette to absorb 0.7M LSMO sol and drop it onto the surface of a 1cm×1cm fluorphlogopite substrate. After spin coating and pyrolysis (pyrolysis temperature is 300℃), the LSMO coating is evenly deposited. Then, the fluorphlogopite substrate with LSMO coating is placed in a tube furnace, and in an oxygen atmosphere with a flow rate of 30mL / min, the temperature is raised to 1000℃ at a rate of 10℃ / min and kept for 1h to crystallize the LSMO coating.
[0100] 2. Repeat the spin coating of PZT sol on the LSMO coating for 20 times to obtain a PZT / LSMO / mica product of target thickness; wherein, after each two spin coatings, the product is placed in a rapid annealing furnace and sintered at 800°C for 6 minutes in an oxygen atmosphere.
[0101] 3. Add polymethyl methacrylate to ethyl lactate, stir in an oil bath at 200°C for 5 hours to obtain a PMMA solution with a mass fraction of 20 wt.%.
[0102] 4. Repeat the spin coating 4 times, wherein the first three baking temperatures are 100°C and the last baking temperature is 120°C, to obtain a solidified flexible support layer with uniform thickness.
[0103] Example 3
[0104] The difference from Example 1 is that in this embodiment:
[0105] 1. Use a pipette to absorb 0.2M LSMO sol and drop it onto the surface of a 1cm×1cm fluorphlogopite substrate. After spin coating and pyrolysis (pyrolysis temperature is 100°C), the LSMO coating is evenly deposited. Then, the fluorphlogopite substrate with the LSMO coating is placed in a tube furnace, and the temperature is raised to 650°C at a rate of 1°C / min in an oxygen atmosphere with a flow rate of 40mL / min and kept for 3h to crystallize the LSMO coating.
[0106] 2. Repeat the spin coating of PZT sol on the LSMO coating for 24 times to obtain a PZT / LSMO / mica product of target thickness; wherein, after each two spin coatings, the product is placed in a rapid annealing furnace and sintered at 600°C for 8 minutes in an oxygen atmosphere.
[0107] 3. Add polymethyl methacrylate to ethyl lactate, stir in an oil bath at 200°C for 7 hours to obtain a PMMA solution with a mass fraction of 5 wt.%.
[0108] 4. Repeat the spin coating 4 times, wherein the first three baking temperatures are 50°C and the last baking temperature is 90°C, to obtain a solidified flexible support layer with uniform thickness.
[0109] Example 4
[0110] This embodiment provides a fully flexible PZT sensor, the manufacturing principle of which is to release the PZT film from a high-toughness mica substrate to a flexible polyethylene terephthalate (PET) substrate, and then develop a lightweight, ultra-sensitive piezoelectric sensor. Specifically, this embodiment uses the fully flexible PZT film obtained in Example 1, and obtains a fully flexible PZT sensor by presetting interdigital electrodes, printing interdigital electrodes on a PET substrate, separating the PZT / PMMA film from the fluorphlogopite mica substrate, transferring the PZT / PMMA film to the PET substrate, and packaging and polarizing. Fig.14 shown.
[0111] The above processes are explained one by one below.
[0112] 1. Design and print interdigitated electrodes on PET substrate
[0113] The PZT / PMMA film structure after etching is very fragile and it is impossible to grow interdigital electrodes on the surface by magnetron sputtering technology. Therefore, an inkjet printer is used to prepare the interdigital electrodes in this embodiment. Specifically, the interdigital electrodes are designed using drawing software (such as AutoCAD, UG, SolidWorks, etc.), where the interdigital spacing is 500 μm, the finger width is 200 μm, the finger length is 7.4 mm, and there are 7 pairs of interdigital electrodes.
[0114] The materials for inkjet printing were PET substrate and conductive silver ink purchased from Beijing Dahua Bo Ke Intelligent Technology Co., Ltd. Each interdigital electrode was printed four times to increase the ink thickness to improve conductivity. After printing, the sample was placed in an oven at 140°C and baked for 20 minutes to remove the ink solvent. Finally, the conductive silver resin was used to connect the wires to the pins of the interdigital electrodes.
[0115] 2. Transfer
[0116] After etching, there is only a weak bonding force between the PZT / PMMA film and the fluorphlogopite substrate. After taking out the sample, carefully scrape off the PMMA on the side with a blade, and then insert the entire sample obliquely into anhydrous ethanol to separate the PZT / PMMA film from the fluorphlogopite substrate with the help of the capillary force of ethanol. Then, immerse the PET substrate printed with interdigital electrodes in anhydrous ethanol, lift up the floating PZT / PMMA film, and complete the transfer.
[0117] 3. Packaging and Polarization
[0118] After the ethanol evaporates, the PZT film is tightly attached to the PET substrate. At this time, 3M double-sided tape is used as the packaging layer, and external force is applied to make it tightly fit on the sample surface to make a patch sensor. Finally, an oil bath polarization method is used to apply a 20kV / cm DC electric field to the sensor, and polarize it at room temperature for 30 minutes (to orient the dipoles to enhance the piezoelectric properties), thus obtaining a fully flexible PZT sensor.
[0119] Sensor electrical performance test:
[0120] 1. Tap test
[0121] Fig.15 The sensing performance of the fully flexible PZT sensor in the compressive load mode is demonstrated, where the force range of the exciter is 0.2-1N, and the external force increases by 0.2N in each test. Fig.15 As shown in (a), as the external force increases, the open circuit voltage of the sensor shows a steady upward trend, and the voltage reaches 8.4V under the condition of 1N force. Fig.15 As shown in (b), the sensitivity of the fully flexible PZT sensor reaches 2.811V / N; at the same time, while ensuring high sensitivity, the fully flexible PZT sensor can still maintain a linear fit of 0.98.
[0122] Fig.16 The fully flexible PZT sensor is used to charge capacitors of different capacities. The AC signal generated by the sensor is Fig.16 (a) The bridge rectifier shown converts it into a DC signal. At a tapping frequency of 10 Hz, the fully flexible PZT sensor can charge a 0.33uF capacitor to 22.5V within 22s; within a charging time of 3min, the fully flexible PZT sensor can charge a 2.2uF capacitor to 4V, proving that the fully flexible PZT sensor has the potential to power micro-nano devices.
[0123] 2. Bending test
[0124] Fig.17 The bending performance test of the fully flexible PZT sensor using the cantilever beam mode is demonstrated. Fig.17 As shown in (a), as the bending angle increases, the open circuit voltage of the fully flexible PZT sensor continues to increase. When the bending reaches 90°, the open circuit voltage can reach 10.2V, and the voltage signal waveform and amplitude are stable during bending. Fig.17 (b) shows that the voltage amplitude has a high positive correlation with the bending angle.
[0125] In addition, in order to verify that the output signal is generated by the piezoelectric effect, the fully flexible PZT sensor is bent upward and downward, and the voltage waveform obtained is as follows: Fig.18In the tensile and compressive force modes, the direction of the voltage signal is reversed, but the amplitude is close, thus ruling out the existence of triboelectric effect.
[0126] Example 5
[0127] This embodiment provides a 3M mask with a breathing monitoring function. The fully flexible PZT sensor prepared in Example 3 is attached to the 3M mask, and can be deformed synchronously with the mask during breathing, thereby realizing breathing monitoring.
[0128] Fig.19 The above 3M mask monitors the breathing status, where: Fig.19 (a) shows the attachment position of the sensor. The subjects simulated four breathing states: fast breathing, normal breathing, coughing, and deep breathing, and obtained four differentiable piezoelectric signals. Fig.19 It can be seen that the average respiratory frequency and amplitude of rapid breathing are 135.4 times / min and 0.5V, respectively, the average respiratory frequency and amplitude of normal breathing are 72.5 times / min and 0.89V, respectively, the average respiratory frequency and amplitude of coughing are 96.8 times / min and 1.08V, respectively, and the average respiratory frequency and amplitude of deep breathing are 36.3 times / min and 1.29V, respectively. The comparison results of rapid breathing and deep breathing show that longer and more powerful inhalation of air (deep breathing) is conducive to the complete deformation of the sensor, which is manifested as an increase in the output signal; the comparison results of rapid breathing and coughing show that, at a faster respiratory rate, there are also signal differences between inhalation (rapid breathing) and exhalation (coughing).
[0129] The above results show that the fully flexible PZT sensor has good discrimination for different breathing states, confirming its feasibility as a breathing sensor.
[0130] Example 6
[0131] This embodiment provides a smart glove, in which the fully flexible PZT sensor prepared in Example 3 is attached to the joints of each finger on the glove and connected to a PCB circuit board. The piezoelectric signal is then transmitted to a smart phone in real time through a Bluetooth module to achieve multi-channel data transmission and recording, thereby achieving real-time gesture recognition.
[0132] like Fig. 20 As shown in the figure, when the index finger, middle finger, ring finger and pinky finger are bent respectively, the corresponding sensors generate corresponding voltage peaks, which do not interfere with the sensors on other fingers. When the five fingers are clenched into a fist, the five sensors generate piezoelectric signals at the same time, proving that the fully flexible PZT sensor can sensitively monitor the bending movement of the fingers. This result shows that the fully flexible PZT sensor is feasible for gesture recognition and monitoring.
[0133] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A method for preparing a fully flexible PZT thin film, characterized in that: The following steps are involved: (1) uniformly depositing an LSMO coating on a fluorophlogopite substrate and crystallizing the LSMO coating; (2) Spin coating several layers of PZT thin film on the crystallized LSMO coating to obtain a PZT / LSMO / mica product; (3) preparing a flexible support layer on the PZT thin film layer; (4) Immersing the product obtained in step (3) in an etching solution to completely dissolve the LSMO coating, thereby obtaining a fully flexible PZT film.
2. The method for preparing a fully flexible PZT thin film according to claim 1, characterized in that: The step (1) comprises the following steps: (101) preparing LSMO sol; (102) 0.2–0.7 M LSMO sol was spin-coated onto the surface of a fluorophlogopite mica substrate and pyrolyzed at 100–300 °C for 10–50 min to uniformly deposit an LSMO coating; (103) The fluorophlogopite substrate deposited with the LSMO coating was placed in a tube furnace and heated to 650–1000 °C at a rate of 1–10 °C / min in an oxygen atmosphere with a flow rate of 30–40 mL / min and kept at this temperature for 1–3 h to crystallize the LSMO coating.
3. The method for preparing a fully flexible PZT thin film according to claim 2, characterized in that: The step (101) comprises the following steps: (1011) 8 mmol of manganese acetate tetrahydrate and an equal mole of acetylacetone were added to 10 mL of anhydrous methanol, stirred to dissolve, and then 5.6 mmol of lanthanum nitrate hexahydrate was added to prepare precursor A; (1012) 2.4 mmol of strontium acetate pentahydrate was added to 5 mL of anhydrous methanol and L-lactic acid was added dropwise at a twice molar ratio. After stirring and dissolving, precursor B was obtained. (1013) Precursors A and B were mixed and diluted to 20 mL with anhydrous methanol. The mixture was magnetically stirred for 8 h and then aged for 24 h to obtain LSMO sol.
4. The method for preparing a fully flexible PZT thin film according to claim 2 or 3, characterized in that: The step (2) comprises the following steps: (201) The PZT sol was spin-coated on the crystallized LSMO coating and the organic solvent in the sol was removed to obtain a PZT thin film layer; (202) Repeat step (201) 20-24 times to obtain a PZT / LSMO / mica product of target thickness; wherein, after each two spin coatings, the product is placed in a rapid annealing furnace and sintered at 600-800° C. in an oxygen atmosphere for 6-8 minutes.
5. The method for preparing a fully flexible PZT thin film according to claim 4, characterized in that: In the step (2), the step (3) includes the following steps: (301) Polymethyl methacrylate was added to ethyl lactate and stirred in an oil bath at 150–200 °C for 5–7 h to obtain a PMMA solution with a mass fraction of 15–20 wt.%. (302) spin coating the PMMA solution onto the surface of the PZT / LSMO / mica product and baking; (303) Repeat step (3) 4 times, wherein the baking temperature for the first three times is 50-100°C and the last time is 90-120°C, to obtain a solidified flexible support layer with uniform thickness.
6. The method for preparing a fully flexible PZT thin film according to claim 5, characterized in that: In the step (4), the etching solution is obtained by mixing high-purity water, hydrogen chloride and potassium iodide.
7. A method for preparing a fully flexible PZT sensor, characterized in that: The following steps are involved: S1. Design interdigital electrodes and print them on PET substrates; S2. Transfer the fully flexible PZT film described in any one of claims 1 to 6 onto a PET substrate, and then package and polarize it to obtain a fully flexible PZT sensor.
8. The method for preparing a fully flexible PZT sensor according to claim 7, characterized in that: The step S1 comprises the following steps: S101. Use drawing software to design interdigitated electrodes, where the interdigital spacing is 500 μm, the finger width is 200 μm, and the finger length is 7.4 mm; S102, using an inkjet printer to print interdigitated electrodes on a PET substrate.
9. The method for preparing a fully flexible PZT sensor according to claim 8, characterized in that: In step S102, the printing ink used is conductive silver ink, and each interdigitated electrode is repeatedly printed 4 times. After printing, the sample is placed in an oven for baking to remove the solvent of the ink.
10. The method for preparing a fully flexible PZT sensor according to any one of claims 7 to 9, characterized in that: In step S2, the process of transferring the piezoelectric film to the PET substrate is as follows: a. Insert the piezoelectric film obliquely into anhydrous ethanol, and separate the PZT / PMMA film from the fluorphlogopite substrate by means of the capillary force of ethanol; b. Immerse the PET substrate printed with interdigital electrodes in ethanol, lift up the floating PZT / PMMA film, and complete the transfer.